2013
DOI: 10.4137/hsi.s11083
|View full text |Cite
|
Sign up to set email alerts
|

Article Commentary: Adolescent Sleep and Cellular Phone Use: Recent Trends and Implications for Research

Abstract: Adolescent sleep needs range from 8.5–10 hours per night, with older adolescents requiring less sleep than younger adolescents. On average, however, American adolescents receive between 7.5–8.5 hours of sleep per night, with many sleeping fewer than 6.5 hours on school nights. Cellular phone use is emerging as an important factor that interferes with both sleep quality and quantity, particularly as smartphones become more widely available to teens. This review paper has three objectives. First, we will describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
3
34
0
Order By: Relevance
“…Text messaging might be expected to improve compliance of teenagers, who remain connected to mobile media at various locations and at all times. 9 A total of 88% of teens have access to cellular phones and 91% of those use text messages on a daily basis. 19 The average adolescent sends 100 texts per day; 9,19 the average duration of smartphone usage is 4.65 hours per day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Text messaging might be expected to improve compliance of teenagers, who remain connected to mobile media at various locations and at all times. 9 A total of 88% of teens have access to cellular phones and 91% of those use text messages on a daily basis. 19 The average adolescent sends 100 texts per day; 9,19 the average duration of smartphone usage is 4.65 hours per day.…”
Section: Discussionmentioning
confidence: 99%
“…5 Compliance is particularly important for teenagers, who are the patients most commonly treated in orthodontics. 4 Text messaging, which has become the primary mode of communication for adolescents, 9 provides a means of increasing compliance. Bowen et al followed patients for 2 months and found that automated weekly text reminders were effective in improving oral hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent consumption of technology, particularly smartphones, has dramatically increased over the past decade [16,24]. In comparison to other age groups, adolescents spend greater amounts of time using technology [25], which is arousing and delays nighttime sleep onset [4][5][26][27].…”
Section: Implications and Contributionmentioning
confidence: 99%
“…Several recent studies have examined nighttime media use, broadly defined (which may include television “screen time” as well as screen time from other types of technology, including cell phones), and adolescent sleep(1, 7, 9-11). For instance, Hale and Guan (7) found that among the 67 studies identified in a review of the literature on screen time and sleep among children and adolescents, 90% showed a significant inverse association between screen time and sleep duration.…”
mentioning
confidence: 99%
“…Importantly, research suggests that trends in the types of technology being used by adolescents are changing at a rapid rate, with increasing “screen time” related to mobile device use(9). In particular, the use of “texting” as a means of communication has risen dramatically among teens.…”
mentioning
confidence: 99%